Sistem Inventaris SMK 1 Pasundan Bandung Berbasis Web - Dewi Rosmala; M Rizqi N; M Iqbal F; M Rakha F; Erwin F; M Alif Rijluddin Y (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
SMK Pasundan 1's Inventory of Goods website is a modern solution to efficiently manage and monitor school inventory. Developed as a tool that supports asset management, the website provides an integrated platform for inventory recording, monitoring, and reporting. Key features include a user-friendly recording system, allowing school staff to easily enter, delete, and update item information.